Pengaruh Model Pembelajaran IOC(Inside Outside Circle) terhadap Hasil Belajar Siswa pada Tema 1 Indahnya Kebersamaan Subtema 2 Kebersamaan Dalam Keberagaman Pembelajaran 1, 2 Dan 3 di Kelas IV SDN 091447 Saribujawa Kecamatan Dolok Panribuan - Pipi Amita Sinaga; Lisbet N. Sihombing; Eva Pasaribu (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine the effect of the IOC (Inside Outside Circle) Learning Model on Student Learning Outcomes on Theme 1 The Beauty of Togetherness Sub-theme 2 Togetherness in Religion in Class IV SDN 091447 Saribujawa, Dolok Panribuan District, 2022/2023 Academic Year.This research is quantitative research with the type of Quasi-Experimental research. The population in this study were all IV grade students at SDN 091447 Saribujawa who collected 52 students and the samples were IVA which found 26 students and IVB class which collected 26 students. Sampling using the Cluster Random Sampling technique. The data collection instrument used was in the form of a multiple choice test. Data analysis was performed using the Independent Sample t-test with the help of IBM SPSS Statistics version 23. The result of this study indicates that the thematic learning outcomes of students who are taught with the IOC (Inside Outside Circle) model have an average post-test score of 80,92 which is in the good category. While the class using the conventional model obtained an average post-test of 71,46 which was in the sufficient category. In the Independent Sample t-test, the value of t_count = 3,724 and Sig. (2-tailed) is 0,000. The value of the t_table distribution based on df = 50 with a significant level of = 0,05 is 2,008. Because the value of t_count > t_table (3,724 > 2,008) and Sig.(2-tailed) 0,000 < 0,05, H_a is accepted and H_0 is rejected. Thus, it can be said that there is a significant effect of the use of the IOC (Inside Outside Circle) Learning Model on the learning outcomes of IV grade students at SDN 091447 Saribujawa.